Climate change and future adaptation - Kajfež-Bogataj, Lučka (Economic and business review, 2009)
This paper provides a summary of the current scientific understanding of the International Panel on Climate Change (IPCC) on the natural and anthropogenic drivers of changes in global climate. It presents an overview of observed changes in the climate system and their relationships with physical processes as well as an overview of projections for future climate changes. A summary of observed climate changes in Slovenia in the last decades is given and future projections are discussed. Europe has warmed by almost 1°C in the last century, faster than the global average. Precipitation has significantly increased in northern Europe, whereas drying has been observed in the Mediterranean. Continuing the observed trend, average precipitation as well as extreme precipitation are very likely to further increase in most of northern Europe whereas precipitation is very likely to decrease in the Mediterranean. The reduction of precipitation in summer in Slovenia is expected to have serious effects, e.g. more frequent droughts, with considerable impacts on horticulture and the availability of water. Adaptationcan reduce vulnerability to climate variability and change. This paper also discusses the appropriate responses to climate change from the mitigation and adaptation points of view.
Keywords: antropogeni vplivi; Evropa; globalno ogrevanje; klimatske spremembe; podnebje